Pengaruh Model Pembelajaran Kuantum Terhadap Hasil Belajar IPA Ditinjau dari Minat Belajar - Nadia Haibatun Nissa; Shafa Salsabyla Anggitania (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2025)
This study aims to analyze the effect of the quantum learning model on students' science learning outcomes by considering their learning interests. Science learning that often focuses on teachers tends to result in low student engagement and suboptimal learning outcomes. The quantum learning model, which integrates social, emotional, and cognitive aspects, offers a more interactive and meaningful approach. This study used a quasi-experimental pretest-posttest control group design with data collected through a learning interest questionnaire and a science learning achievement test. The results showed that the quantum learning model significantly improved science learning outcomes, especially in students with high learning interests. This finding indicates that students' learning interests can strengthen the effectiveness of implementing the quantum learning model. Based on these findings, it is recommended that educators use the quantum learning approach to create a more engaging, motivating, and student-centered learning environment.